Mild Benzylic Monobromination of Methyl Toluates in Aqueous CTAB - Reddy, Kancharla Rajendar; Rajanna, Kamatala C.; Venkateswarlu, Marri; Saiprakash, P. K. (Synlett, 2014)
A strategy has been developed for the regioselective monobromination of methyl toluates by using tert-butylhydrogen peroxide and potassium bromide (TBHP/KBr) in a cetyltrimethylammonium bromide (CTAB) micellar medium. Ultrasonic and microwave-assisted protocols recorded increased rates and product yields under mild reaction conditions, coupled with a straightforward isolation procedure.
Keywords: bromination; monobromo methyl toluates; cetyltrimethylammonium bromide; microwaves; ultrasound